Mithras, Neoplatonism and the stars - Ionescu, Dan-Tudor (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The main ideas of this study (which is a continuation of my former article entitled “Mithras, Sol Invictus, and the Astral Philosophical Connections”) are the following: I. The dichotomy and differences between the two main groups of theories regarding the origins of the Roman mystery cult of Mithras, namely the school of the great Belgian scholar Franz Cumont, who considered Mithraism in the Roman world as an essentially Iranian cult adapted to the new cultural Hellenistic-Roman context, and the theory of the 19th century German scholar K. B. Stark (revived in the 1970s by academics like R. Beck, J. R. Hinnells, S. Insler, R. Gordon, and A. Bausani, who considered that the Roman cult of the solar god Mithras was a new mystery cult which was born in the Roman world because of the Hellenistic scientific discovery of the precession of the equinoxes.1 My conclusion is that the Roman cult of Mithras, fused with the cult of Sol Invictus (the Hellenistic-Roman cult of the Unvanquished Sun), has more things Iranian than the name of the central deity of this initiation-mystery cult (despite its undeniable Hellenistic-Roman and astrological-astronomical elements). II. The astral element as a potent religious component of the religious and philosophical mentality of the so-called “mystery religious and initiation cults” in the Roman Empire is seen in Roman Mithraism as a ladder for the journey of the soul through the astral spheres towards perfection or possibly towards liberation (these are modern interpretations, since we do not have any consistent Mithraic religious-liturgical text). III. The role of Neo-Platonist philosophy in the religious and philosophical landscape of the 3rd and 4th centuries CE of the Late Roman Empire and its possible relationship with the Roman cult of Mithras.